2021
DOI: 10.1093/mnras/stab127
|View full text |Cite
|
Sign up to set email alerts
|

SPIDERS: an overview of the largest catalogue of spectroscopically confirmed x-ray galaxy clusters

Abstract: SPIDERS is the spectroscopic follow-up effort of the Sloan Digital Sky Survey IV (SDSS-IV) project for the identification of X-ray selected galaxy clusters. We present our catalogue of 2740 visually inspected galaxy clusters as part of the SDSS Data Release 16 (DR16). Here we detail the target selection, our methods for validation of the candidate clusters, performance of the survey, the construction of the final sample, and a full description of what is found in the catalogue. Of the sample, the median number… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 69 publications
0
16
1
Order By: Relevance
“…Better constraints on the velocity dispersion are obtained using scaling relations of LX −M200 (Leauthaud et al, 2010) and M200 − σv,VT (Carlberg et al, 1997). The lognormal scatter LX − σv,VT relation is measured to be 0.13 by Kirkpatrick et al (2021). Using the velocity dispersion from scaling relations, the disagreement with simulations consists in a wider tail above 0.7σ extending to 2.5σ.…”
Section: Comparison With Cosmological Simulationsmentioning
confidence: 98%
“…Better constraints on the velocity dispersion are obtained using scaling relations of LX −M200 (Leauthaud et al, 2010) and M200 − σv,VT (Carlberg et al, 1997). The lognormal scatter LX − σv,VT relation is measured to be 0.13 by Kirkpatrick et al (2021). Using the velocity dispersion from scaling relations, the disagreement with simulations consists in a wider tail above 0.7σ extending to 2.5σ.…”
Section: Comparison With Cosmological Simulationsmentioning
confidence: 98%
“…Redshift measurements of the individual galaxies in the cluster field clearly separate the cluster members and interlopers. Previous studies compile spectroscopic redshift measurements of galaxies in clusters identified by other methods (e.g., X-ray, optical, and IR imaging) to refine these cluster catalogs (e.g., Rozo et al 2015;Clerc et al 2016;Sohn et al 2018a,b;Rines et al 2018;Myles et al 2020;Kirkpatrick et al 2021). Other studies identify galaxy overdensities or, equivalently, clusters in redshift space (e.g., Huchra & Geller 1982;Eke et al 2004;Berlind et al 2006;Robotham et al 2011;Tago et al 2010;Tempel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The trends in velocity bias discussed in this work are all empirically testable with ongoing spectroscopic campaigns of clusters such as SPIDERS (Kirkpatrick et al 2021) and DESI. The dependence of 𝜎 sat, 1D on 𝑀 ★, sat (or more precisely, the galaxy luminosity) has already been observationally studied for many different modestly-sized samples of clusters (𝑁 ∼ 100) as was noted before, while such observational studies of the redshift and halo mass trends have not yet been well-explored.…”
Section: Discussionmentioning
confidence: 61%
“…For example, Bocquet et al (2015, see Section 3 and Section 5.1) discuss that a 1% prior on the velocity bias improves constraints on both astrophysical and cosmological parameters connected to galaxy clusters by ≈ 30%. Cluster counts as a function of their galaxy velocity dispersion and redshift has also emerged as an alternative approach for cluster cosmology (Caldwell et al 2016;Ntampaka et al 2017Ntampaka et al , 2019Kirkpatrick et al 2021), and the velocity bias is a critical component in forward modelling the relevant observable from cosmological parameters. 4), and the fractional uncertainty on each estimate (right panel).…”
Section: Revised Mass Scale Of Low-𝑍 Sdss Clustersmentioning
confidence: 99%